The non-linear relationship between sum of 7 skinfolds and fat and lean mass in elite swimmers - Mitchell, L. J. G.; Morris, K. S.; Bolam, K. A.; Pritchard-Peschek, K. R.; Skinner, T. L.; Shephard, M. E. (Journal of Sports Sciences, 2020)
Body composition can substantially impact elite swimming performance. In practice, changes in fat and lean mass of elite swimmers are estimated using body mass, sum of seven skinfolds (Summe7) and lean mass index (LMI). However, LMI may be insufficiently accurate to detect small changes in body composition which could meaningfully impact swimming performance. This study developed equations which estimate dual-energy x-ray absorptiometry (DXA)-derived lean and fat mass using body mass and Summe7 data. Elite Australian swimmers (n = 44; 18 male, 26 female) completed a DXA scan and standardised body mass and Summe7 measurements. Equations to estimate DXA-derived lean and fat mass based on body mass, Summe7 and sex were developed. The relationships between Summe7, body mass and DXA-derived lean and fat mass were non-linear. Fat mass (Adjusted R2 = 0.91; standard error = 1.0 kg) and lean mass (Adjusted R2 = 0.99; standard error = 1.0 kg) equations were considered sufficiently accurate. Lean mass estimates outperformed the LMI in identifying the correct direction of change in lean mass (82% correct; LMI 71%). Using the accurate estimations produced by these equations will enhance the prescription and evaluation of programmes to optimise the body composition and subsequent performance in swimmers.